Informal possibilities in adult education: civic organizations and conferences - Szabados, György; Wiwczaroski, Troy; Móré, Mariann (Acta Scientiarum Socialium, 2012)
Currently, the educational system is not only a major focus of public attention, but expectations for its future are also rising. In today’s economic circumstances, it has become obvious that for uneducated and only slightly educated individuals, particu-larly for those with little work experience, their chances in the labor market are slim to none. Instead of gainful employment, their lives are based on a vulnerability of being supported by government aid and public employment projects – neither of which are guaranteed over time. Risk is also high for highly qualified employees, as rising and continuously changing expectations force these workers to seek new qualifications, as well as to look for venues for maintaining and enhancing their knowledge. The objective of adult education is to replace and supplement existing knowledge and practice. In addition to formal educational means, non-formal and informal solutions are increasingly widespread. Regarding practices, diverse civic organizations play a growing role in alternative educational activities. This sphere is composed of a variety of types of organizations; the introduction of a new act and the related regulative background will certainly change the character of this sector, the activity of which has already been debated on many forums. Numerous private or quasi-private civic organizations live – in a kind of symbiosis – with many higher education institutions. The most important functions of these civic organizations are to promote greater access to knowledge or experience for freshly graduated adults, supplementing the results of higher education or ensuring the dissemination of educa-tional or research results and the mutual exchange of experiences among lecturers and researchers, by organizing meetings and conferences. The aim of our research is to analyze and expose the motivation, professional and human backgrounds, informal adult education activity and the sustainability of selected civic organizations involved in the organization of adult education conferences and publications. The examinations mainly focus on the practice of those civic organizations operating alongside higher education institutions. Elements of the sample include civic program managers involved in the examined activity. The research method consists of a survey, a case study and private observations. We believe that the examined civic organizations frequently offer solutions which are unattainable for basic institutions (such as specific funds) or that the dissemination they offer is implemented on a higher level (publication in more important and preferred journals, publications). Such activity does not represent an outsourcing solution by higher education institutions, but is rather a novel, high quality solution in the face of changing job market conditions.